Long-Term Trends in Estuarine Carbonate Chemistry in the Northwestern Gulf of Mexico - McCutcheon, Melissa R.; Hu, Xinping (Frontiers in Marine Science, 2022)
A four-decade dataset that spans seven estuaries along a latitudinal gradient in the northwestern Gulf of Mexico and includes measurements of pH and total alkalinity was used to calculate partial pressure of CO2 (pCO2), dissolved inorganic carbon (DIC), saturation state of aragonite (ΩAr), and a buffer factor (βDIC, which measures the response of proton concentration or pH to DIC concentration change) and examine long-term trends and spatial patterns in these parameters. With the notable exception of the northernmost and southernmost estuaries (and selected stations near freshwater input), these estuaries have generally experienced long-term increases in pCO2 and decreases in DIC, ΩAr, and βDIC, with the magnitude of change generally increasing from north to south. At all stations with increasing pCO2, the rate of increase exceeded the rate of increase in atmospheric pCO2, indicating that these estuaries have become a greater source of CO2 to the atmosphere over the last few decades. The decreases in ΩAr have yet to cause ΩAr to near undersaturation, but even the observed decreases may have the potential to decrease calcification rates in important estuarine calcifiers like oysters. The decreases in βDIC directly indicate that these estuaries have experienced continually greater change in pH in the context of ocean acidification.